Peningkatan Hasil Belajar Luas Bangun Datar Menggunakan Model Jigsaw di SDN 21 Limau Sundai - Narti, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aims to describe the use of jigsaw type cooperative learning model to improve the learning outcomes widescreen flat in class V SDN 21 Limau Sundai Batang Kapas. The subjects of this study are researchers as teachers who teach, and students who numbered 24 people. The type of research is classroom action research. This research shows that in cycle I, the average 67,85 cycle II increased to 89,28. Activity of teacher of cycle I got an average of 70, and cycle II increased to 95. Student activity of cycle I got an average of 67,5, and cycle II increased to 90. Result of learning cycle I cognitive, affective and psychomotor aspect got average 70 and cycle II increased to 80.41. It can be concluded that the use of jigsaw type cooperative learning modl can improve the widespread learning outcomes. Keywords: Learning outcomes, wake up flat, jigsaw